Implementasi dan Analisis Connector Wire Testing Machine Berbasis PID dan Antarmuka Visual - Diono; Muhammad Syafei Gozali; Indra Mora (JURNAL INTEGRASI, 2026)
In the era of Industry 4.0, automation in the quality testing process has become a crucial factor in ensuring production consistency, accuracy, and efficiency. This research develops a connector wire testing machine that integrates a load cell sensor, a servo motor control system based on a proportional - integral-derivative (PID) controller, a real-time visual interface developed in C#, and a SQL Server database for automated data logging. Load cell calibration was performed by comparing sensor readings with a digital reference scale over a load range of 1 kg to 3 kg. The results show that the measurement deviation remained below ±0.2%, indicating that the load cell provides accurate and consistent force measurement. Communication performance between the ESP32 and the C# graphical user interface was evaluated through bidirectional latency testing. The system achieved an average delay of 2.2 ms, which is well below the industrial response time threshold of 100 ms, demonstrating stable and responsive data transmission. Database performance testing showed a success rate of 100%, a duplicate rate of 0%, and a coefficient of variation (CV) of 11%, confirming reliable and stable real-time data processing. Furthermore, PID controller tuning resulted in optimal parameters of KP = 0.0025, Ki = 0.00015, and Kd = 0.003, which produced low overshoot (<1%), minimal steady-state error (<0.3%), and relatively short settling times across various setpoints. Overall, the developed system operates accurately, responsively, and reliably, supporting precise wire connector pull testing and robust data management for further analysis and continuous quality improvement.